2020
DOI: 10.3390/su12093704
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Regime Shifts and Their Potential Drivers in the Shallow Eutrophic Lake Yilong, Southwest China

Abstract: Regime shifts in shallow lakes can lead to great changes in ecosystem structures and functions, making ecosystem management more complicated. Lake Yilong, located in Yunnan Province, is one of the most eutrophic lakes in China. Although there is a high possibility that this lake has undergone regime shift one or more times, the presence of regime shifts and their drivers remain unknown. Here, we employed the sequential t-test analysis of regime shifts to detect the regime shifts based on the long-term (1989–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Thus, Chl-a is an important indicator used for investigating eutrophication, and it plays a key role in the evaluation of the nutritional status of the lake water. It was found that Chl-a in Lake Yilong changed with seasons [40][41][42].…”
Section: Seasonal Variations Of Chlorophyll-amentioning
confidence: 99%
“…Thus, Chl-a is an important indicator used for investigating eutrophication, and it plays a key role in the evaluation of the nutritional status of the lake water. It was found that Chl-a in Lake Yilong changed with seasons [40][41][42].…”
Section: Seasonal Variations Of Chlorophyll-amentioning
confidence: 99%
“…Lakes are one of the most important freshwater resources in the world. Grass-type and algae-type lakes represent different stages in the lake succession process, with macrophytes and algae being the primary producers of the two stages, which are mutually inhibited [1][2][3]. Due to the increasing intensity of development and the utilization of resources in lake basins in recent years, a series of ecological and environmental problems have arisen in some lakes [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, such studies can identify both the loss and recovery of ecosystem resilience [10]. Additionally, tracking the extent of changes in traits may provide insight into how communities rebound either by hysteretic or non-hysteretic pathways [10,11] and also may provide information about the subtle changes indicating a regime shift that ultimately leads to alternative stable states [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%